Translating political discourse : a comparative study of Chinese-English translation of political texts in Singapore (2009 - 2015) - Tay, Meng How (2017)
In Singapore, misinterpretations leading to mistranslations happen often even in the media for the public. In recent years, there is a gradual transformation of political discourse, which is reflected by changes of discourse through translation. Hence, the National Translation Committee (NTC) was formed in 2014 to oversee short-term and long-term plans to enhance whole-of-government translation capabilities and raise translation standards in Singapore. This paper seeks to examine how political discourse is translated in Singapore by using a corpus data formed by seven sets of Chinese National Day Rally (NDR) speeches and their corresponding English translations. They are analysed using the Skopos Theory and approaches such as Critical Discourse Analysis (CDA) and political equivalence. The implications of translation strategies used, discourse patterns of source texts (STs) and corresponding target texts (TTs) as well as equivalence levels between STs and TTs are identified. The results from such a comparative study will be beneficial for future studies in political discourse translation as well as translation in general. Keywords: Translation, Political Discourse, Skopos Theory, Critical Discourse Analysis, Political Equivalence